THE EFFECT OF GREEN TRANSFORMATIONAL LEADERSHIP AND GREEN HUMAN RESOURCE MANAGEMENT ON ENVIRONMENTAL PERFORMANCE WITH GREEN INNOVATION AS A MEDIATING VARIABLE AT PT INDUKSARANA KEMASINDO IN JAKARTA - Nilam, Edric Budiman; Pangaribuan, Christian Haposan; Thaib, Danial (Ridwan Institute, 2024)
This study aims to analyze the influence of Green Transformational Leadership (GTL) and Green Human Resource Management (GHRM) on Environmental Performance and Green Innovation, as well as the relationship between Green Innovation and Environmental Performance. This study uses a quantitative approach with the partial least squares structural equation modeling (PLS-SEM) analysis method, with Green Innovation as the mediating variable. The study uses primary data collected through questionnaires from 110 employees of PT Induksarana Kemasindo. The results show that GHRM and GTL have a significant role in improving environmental performance and green innovation (Green Innovation) at PT. However, Green Innovation does not function as a significantly mediator between GTL, GHR, and environmental performance. As a practical suggestion, companies need to improve the effectiveness of the GTL by integrating environmental sustainability principles into all aspects of human resource management and creating a work environment that supports Green Innovation.